Earthquakes as a coupled shear stress high pore pressure dynamical system - Miller, Stephen Andrew; Nur, Amos; Olgaard, David L. (My University, 1996)
The migration, coalescence and localization of slip, seismicity, and zones of high pore pressure are modeled using a porosity reduction mechanism to drive pore pressure within a fault zone in excess of hydrostatic. Increased pore pressure in discrete cells creates zones of low effective stress, which induces slip that may propagate to surrounding cells depending on the local state of stress. At slip, stress is transferred using the solution for a rectangular dislocation in an elastic half-space, and pore pressures are redistributed by conserving fluid mass. Using simple assumptions about fault rheology and permeability, it is shown that the interaction between shear stress and effective stress evolves to a state of earthquake clustering with repeated events, locked zones, and large variations in fault strength. The model evolves from a uniform shear stress state on a strong fault, to a heterogeneous shear stress state on a weak fault.